New Structured Illumination Technique for the Inspection of High-Reflective Surfaces: Application for the Detection of Structural Defects without any Calibration Procedures. (25th March 2008) - Caulier, Yannick; Spinnler, Klaus; Bourennane, Salah; Wittenberg, Thomas
Abstract : We present a novel solution for automatic surface inspection of metallic tubes by applying a structured illumination. The strength of the proposed approach is that both structural and textural surface defects can be visually enhanced, detected, and well separated from acceptable surfaces. We propose a machine vision approach and we demonstrate that this technique is applicable in an industrial setting. We show that recording artefacts drastically increases the complexity of the inspection task. The algorithm implemented in the industrial application and which permits the segmentation and classification of surface defects is briefly described. The suggested method uses "perturbations from the stripe illumination" to detect, segment, and classify any defects. We emphasize the robustness of the algorithm against recording artefacts. Furthermore, this method is applied in 24 h/7 day real-time industrial surface inspection system.